Odpowiedź:
z.1
a) P = (2 , - 4)
y = a [tex]x^{2}[/tex] więc - 4 = a*2^2
- 4 = 4 a
a = - 1
Odp. y = - x^2²
b) y = a [tex]x^{2}[/tex] więc 1/4 = a *( -1/2)^2
1/4 = (1/4)*a
a = 1
y = x^2
=======
c) analogicznie.
z.2
a) f(x) =2 x² [ 0, - 5 ]
g(x) = 2*( x - 0)² - 5 = 2 x^2 - 5
===========================
b) f(x) = - 3 x² [ 2, 0 ]
g(x) = -3 *( x -2)² + 0 = - 3*( x - 2)²
c) f(x) = [tex]\frac{1}{2}[/tex] x² [ - 1 , 3 ]
g(x) = [tex]\frac{1}{2}[/tex] *( x + 1)² + 3
=================
Szczegółowe wyjaśnienie: